Pengaruh Kreatifitas dalam bekerja terhadap kebermaknaan hidup - Rahmat Aziz; Retno Mangestuti (Program Studi bimbingan Konseling PPs UNM Makassar, 2018)
This study aimed to examine the direct effect of creativity on the meaning of life, and an indirect effect through performance. Subjects were 186 teachers (113 male and 73 female). The data were collected by the creativity scale, the job performance scale, and the meaning in life scale. The data were analyzed by moderated regression analysis. The results showed that performance play a role in strengthening the relationship between creativity and the search for a meaningful life (p <.01), but not in the relationship between creativity and the presence of meaning of life (p> .05).